BUS STOP AS A VISUAL DYNAMIC SYSTEM: WAYS OF THE VISUAL DYNAMIC CREATION - Скляренко, Н. В.; Колосніченко, М. В. (Art and Design, 2021)
The purposeof the study is to find the ways of the creation of the dynamic visual communications on bus stops. It will make the interaction of the message, a human and the environment harmonious. Methodology.The work is based on the system approach. It makes possible to consider dynamic visual communications as the integral area for the communication of a human and the environment. The results of the compositional and structural and functional analysis helped to make the generalization and systematization of the ways for the visual dynamic creation on bus stops. Results. In the study we consider the bus stop as the visual dynamic system with the intensive communicational processes, which are based on the integration of different forms of human sensitive experience and the urban environment. We proved that subject-visual, visual-sound, visual-tactile and digital visual communications substantiate the transformation of the information perception and deepen it. At the same time a human becomes a part of the communication. Bus stop turns into the experimental location and provides increased emotionality of the communicational processes due to the forming of the immersive context. The designer can afford to program the people’s behavior in the system of the visual dynamic communications. It allows creating opportunities for the stationary bus stops to adapt to the changing external living conditions. Scientific novelty.In the work we rethink the role of the visual communication in the bus stop structure and in the whole environment. The visual communication has an experimental nature. It proves that the communications in the environment are developing towards the increasing dynamics and immersion. Practical significance. The results of the study show the ways to increase the level of dynamics of the visual communications on bus stops. It will make the perception of the informational messages more effective and will make the urban environment more aesthetic. The features of the dynamical designing, which were found, can be used by specialists with the purpose of the designing of the modern environment. In addition, they can be used as the educational technology to form the system thinking of designers.